THE IMPACT OF SOCIAL SCIENCES TEACHER CREATIVITY IN IMPROVING STUDENT MOTIVATION AND LEARNING OUTCOMES AT MTSN 1 LAMONGAN - Ahmad Dzulfikkar Nurriaab; Umi Julaihah (SOSIOEDUKASI, 2026)
This study aims to analyze the influence of social studies teacher creativity and learning motivation on student learning outcomes and the role of learning motivation as a moderating variable at MTsN 1 Lamongan. This study used a mixed method with an Explanatory Sequential Design model and involved 158 eighth grade students as the research sample. Data were collected through questionnaires, interviews, observations, and documentation, then analyzed using SmartPLS 4 and qualitative descriptive analysis. The results showed that social studies teacher creativity had a positive and significant effect on student learning outcomes with a p-value of 0.011 (<0.05), learning motivation had a positive and significant effect on student learning outcomes with a p-value of 0.019 (<0.05), and learning motivation was able to moderate the relationship between social studies teacher creativity and student learning outcomes with a p-value of 0.028 (<0.05). The interview results showed that teacher creativity through the use of digital media, learning videos, group discussions, and contextual approaches was able to improve student motivation and learning outcomes.